Electrical Properties of LaS‐TaS2 Misfit Layered Compound Nanotubes. Issue 3 (15th October 2021) - Stolovas, Dalit; Popovitz‐Biro, Ronit; Sinha, Sudarson S.; Bitton, Ora; Shahar, Dan; Tenne, Reshef; Joselevich, Ernesto
Abstract: Several nanotubular structures from chalcogenide‐based misfit layer compounds (MLC) were reported in recent years. MLCs consist of a stacking of two alternating and dissimilar (2D) atomic layers, e. g. one with rocksalt structure (MX) and the other‐ TX2 – with hexagonal layer structure. The layers are held together by weak van der Waals forces, i. e. they can be exfoliated with scotch‐tape. Furthermore, in analogy to intercalation compounds, partial charge transfer between the layers with dissimilar work function results also in polar forces between the MX and TX2 layers. The mismatch between the alternating (asymmetric) layers and the seaming of the dangling bonds at the edges drives them to form tubular (and also scroll‐like) structures. New structural characterization whereby the nanotubes were bisected into lamella via focused ion beam and examined by TEM, are reported. Abstract :